ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANG PADA TOKO YOORINAIL SURABAYA - Angelina, Marcella; Santi, Chitra (Universitas Widya Kartika Surabaya, 2024)
Companies currently really need an Accounting Information System (AIS) in the running of a business. This research aims to determine the accounting system for merchandise inventory in managing inventory to avoid stock discrepancies, as well as to find out whether the online sales system at the Yoorinail Surabaya Store has been fulfilled properly or not. This type of research is qualitative descriptive research. Where data collection techniques are carried out using interviews, documentation and observation data. The data source used is a primary data source or in other words getting data directly from the company. The results of research at the Yoorinail Surabaya Store show that the merchandise inventory accounting system at the Yoorinail Surabaya Store does not automatically bind stock to the online application, therefore researchers recommend using the Ginee platform as a tool in managing/tying up merchandise inventory online. And stock differences often occur in the merchandise inventory system at the Yoorinail Surabaya Store. Therefore, it is necessary to update the system effectively and efficiently, by storing and sending photo archives of proof of the release of goods in accordance with the sales invoice via WhatsApp.